Persistent Iliosacral Joint Syndrome following Instrumentation to the Sacropelvis in Patients with Adult Spinal Deformity - Diesing, Daniela; Franke, Joerg; Tschoeke, Sven Kevin; Schultheiß, Rolf; Scheufler, Kai Michael (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
Background and Objective Persistent sacroiliac joint syndrome (PSIJS) may complicate adult spinal deformity surgery (ASDS). This study assesses the relationship between clinical/morphometric parameters and PSIJS following ASDS including pelvic fixation and the therapeutic efficacy of secondary iliosacral fusion (ISF).Methods Perioperative health-related quality of life (HRQOL) outcomes (Oswestry Disability Index, Short Form 12-item health survey, version 2 scores) at 6, 12, and 24 months, and radiographic studies were analyzed retrospectively in a cohort of 71 consecutive patients undergoing ASDS. PSIJS was confirmed in nine individuals (12.7%) by placebo-controlled dual sacroiliac joint (SIJ) blocks. The relationships between global and regional spinopelvic morphometry, PSIJS, and HRQOL outcomes were assessed by logistic regression and receiver operating characteristic curve (ROC) analysis.Results PSIJS, independently causing significantly reduced improvement in HRQOL scores (p < 0.001) 6 months postoperatively, warranted secondary ISF in nine patients (12.7%) within 12 months of index surgery, without evidence of progressive SIJ arthrosis, pseudarthrosis, or hardware issues. Eight of nine patients undergoing secondary ISF reported≥ 70% pain reduction at 24 months. Logistic regression/ROC analysis revealed a close association between PSIJS and nonharmonious postoperative L4–S1 fractional lordosis (p < 0.0001), pelvic incidence angle > 53 degrees, hip arthrosis, and preexistent advanced SIJ arthrosis (p < 0.01).Conclusion PSIJS may negatively impact the clinical outcome of ASDS. Recurrent preoperative SIJ syndrome requiring interventional treatment, preexisting hip and SIJ arthrosis, insufficient restoration of L4–S1 fractional lordosis, and high pelvic incidence predispose to PSIJS. PSIJS may potentially be avoided by restoring physiologic lumbosacral geometry and S2 sacral alar-iliac screw fixation during index surgery. Secondary ISF appears to be effective in reducing pain and physical impairment due to PSIJS.
Keywords: sacroiliac joint syndrome; adult spinal deformity; pelvic fixation; iliosacral fusion